Go do! : for people who have always wanted to start a business - Harbour, Jeremy (Chichester, West Sussex : Capstone/John Wiley & Sons Ltd., 2012)
'A refreshingly simple, easy-to-read guide to getting started in businessIf you've ever dreamed of starting your own business, this book will give you the information, inspiration, and reassurance you need to get started. It encourages budding entrepreneurs to take the leap into the dark, while shining a bright light on the first six months of a successful start-up. It breaks down what appears to be an Everest-size challenge into a series of small hills for you to conquer. Written by successful entrepreneur Jeremy Harbour, Go Do! argues that the skills and tactics of successful entrepreneurship can't be learnt except by doing. So this book offers the guidance and the confidence you need to just go do it'--
'In this straight talking, hugely inspiring book Jeremy Harbour explodes these myths, proving that while failure is always a possibility, there's no better time to confront your fears, plan for success, and get started'--
Includes index.
Keywords: New business enterprises -- Management; Entrepreneurship